The satirical press in francophone Africa : analysis of discursive and iconotextual practices in eight West African satirical newspapers - (:unkn) unknown (My University, 2024)
This thesis aims to deeply explore the satirical press in francophone West Africa, focusing on socio-discursive and icono-textual practices. Our interest in this research is reinforced by the growing importance of satire as a means of social and political expression and critique. Studying the satirical press is of great interest as it allows for an understanding of local sociopolitical and cultural dynamics, as well as the modes of expression of humour and critique in multilingual and multicultural contexts. It also offers a perspective on how satirical media influence and reflect public opinion. To understand the socio-discursive and iconotextual practices, the adopted methodology is based on a comparative analysis of a corpus composed of eight satirical newspapers: Le Lynx, Bingo!, Gbich!, L’Eléphant déchaîné, Journal du jeudi, Sika’a, Le Déchaîné du jeudi et le P’tit railleur sénégalais. The theoretical framework employs tools from discourse analysis, sociolinguistics, and semiotics, allowing for an in-depth understanding of the diverse journalistic and stylistic practices. The analyses revealed the importance of national political topics on the front pages of the studied newspapers; we also note that the mix of French and African languages is also used as a powerful means of expressing humour and satire. This thesis has also highlighted distinct discursive practices and stylistic singularities among the different newspapers, such as verbal violence or the use of noun forms of address in local languages in the Bingo newspaper. Additionally, the critical and satirical aims of caricature and photographic practices emerged as key elements. The presence of fictional characters in caricatures and comics also underscores the creative richness of these media. This study thus contributes to a better understanding of the specificities of the satirical press in Francophone Africa, highlighting the diversity of practices and satirical expression
Keywords: African Research